INTENSI KONSUMEN TERHADAP KOSMETIK DAN PRODUK SKINCARE HALAL DI INDONESIA: PENDEKATAN THEORY OF PLANNED BEHAVIOR - Indah Wahyuningsih (Universitas YARSI, 2019)
This study aims to analyze the factors that influence consumer intention to halal cosmetics andskincare products in Indonesia. Data were collected through questionnaires, 120 responses were obtained from halal cosmetics and skincare products consumers in Indonesia. This study uses quantitative and explanatory methods which are analyzed using multiple linear regression with the SPSS software. The results showed that the attitude, subjective norms and perceptions of behavioral control positively and significantly influenced the intention of consumers to buy cosmetics and halal skincare products in Indonesia. By learning the intention of consumers can understand the market potential of the cosmetics and skincare products industry so that it can stimulate the growth of the cosmetics and skincare products industry in Indonesia and the world.